MEMBANGUN KARAKTER PEMBAWA DAMAI: IMPLEMENTASI MATIUS 5:9 DALAM PENDIDIKAN KARAKTER KRISTEN - Illu, Jonidius; Gulo, Eliyunus; Keluanan, Yane Henderina; Istiati, Istiati (STT-RAI Batam, 2025)
Human beings often create social conflicts, preventing the establishment of peace, and those who incite discord are referred to as children of the devil. In general, conflicts arise due to social and cultural tensions that influence character and the impact of family environments. Matthew 5:9 emphasizes that peacemakers are not merely those who avoid conflict but also those who actively foster harmony and reconciliation. The character of a peacemaker reflects the identity of being children of God, which means having Christlikeness in the practice of peacebuilding. This study demonstrates that implementing Matthew 5:9 in Christian character education is highly relevant for shaping individuals to become agents of peace in a world full of conflict. The purpose of this research is to examine Christian character education values related to peace, such as love, forgiveness, and reconciliation, and to explore how these principles can be applied in daily life. This study employs a qualitative method. It emphasizes that the character education taught by Jesus Christ is a character-based teaching centered on His example. The findings of this study affirm that Matthew 5:9 holds strong relevance for Christian character education. The values of peace can be internalized in the lives of Christians, enabling them not only to understand the concept of peace but also to practice it in their daily lives.